Apakah Kamu Peduli Lingkungan? Implementasi Teori Planned Behavior Pada Minat Beli Konsumen Hotel Ramah Lingkungan di Indonesia - Rahayu, Isyana; Herdiyanti, Herdiyanti; Sakinah, Querida Leisya; Mutaqin, Husni Zaini (Fakultas Seni Rupa dan Desain ITB, 2025)
Green hotels are one of the products of sustainable tourism. The theory of planned behavior (TPB) could be a valuable approach for understanding consumer behavior, including visitors' preferences for eco-friendly choices. By looking at sociopsychological components, TPB makes a difference in anticipation, such as tourists' choices to visit green goals or remain eco-friendly. This study aims to examine consumer behavior regarding their interest in staying at a green inn, using the theory of planned behavior (TPB). The research focused on testing the variables of attitude, subjective norm, and perceived behavioral control on customer purchase intention. Data collection was conducted through a questionnaire analyzed by SEM-PLS to determine the causal relationship among latent variables contained in the structural equation with a sample of 121 people who stayed or had stayed at Hyatt Regency Hotel Yogyakarta. The research shows that there is a significant influence among the variables of attitude, subjective norm, and perceived behavioral control on customer purchase intention.